Representation of Human Life in Suicide Silence’s You Only Live Once Music Video - Gibran, Muhammad Zahran (LPPM Universitas Bumigora Mataram, 2025)
Music is delivered through audio and in the form of a video called a Music Video. Music videos serve as a marketing tool and often as a means of open expression to the general public. This study aims to describe the relationship between signs and meanings in the music video You Only Live Once by Suicide Silence. This research employs a descriptive qualitative method to describe data analysis relevant to the topic matter of the study. Based on the result, it can be concluded that the signs contained in the You Only Live Once music video by Suicide Silence. Signs in the music video that represent the human struggle in social life include humans entering a new phase in social life, differences and diversity in each individual, some security forces who abuse their power over the community, mad scientists who abuse their intelligence for their interests, the needs and requests of the child, the practice of prostitution in social life, criminals who are ready to disrupt the security. This elder generation disagrees with the younger generation, the wife’s demands and needs, and death, which can occur at any time.